2008
DOI: 10.1074/jbc.m709417200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of G551D-CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) Potentiation by a High Affinity ATP Analog

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel gated by ATP binding and hydrolysis at its nucleotide binding domains (NBD). The NBDs dimerize in a head-to-tail configuration, forming two ATP binding pockets (ABP) with the ATP molecules buried at the dimer interface. Previous studies have indicated that ABP2, formed by the Walker A and B motifs of NBD2 and the signature sequence of NBD1, is the site critical for the ATP-dependent opening of CFTR. The G551D mutation in ABP2, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…1A shows the effect of 1 mM dATP and 1 mM 3-dATP on G551D-CFTR currents pre-activated with ATP plus PKA. Upon removal of ATP plus PKA, the current remains unchanged as reported previously (14,15). Application of 1 mM dATP enhanced G551D-CFTR currents by 7.7 Ϯ 0.6-fold (n ϭ 12), and the potentiation effect was readily reversible when dATP was removed.…”
Section: G551d-cftr Gating By 2ј-and 3ј-deoxy-atp-supporting
confidence: 53%
See 3 more Smart Citations
“…1A shows the effect of 1 mM dATP and 1 mM 3-dATP on G551D-CFTR currents pre-activated with ATP plus PKA. Upon removal of ATP plus PKA, the current remains unchanged as reported previously (14,15). Application of 1 mM dATP enhanced G551D-CFTR currents by 7.7 Ϯ 0.6-fold (n ϭ 12), and the potentiation effect was readily reversible when dATP was removed.…”
Section: G551d-cftr Gating By 2ј-and 3ј-deoxy-atp-supporting
confidence: 53%
“…The doseresponse relationship for P-dATP (Fig. 2D) demonstrates that the apparent affinity for P-dATP is indeed similar to that of P-ATP on G551D (15). The effect of P-dATP in WT channels is shown in supplemental Fig.…”
Section: G551d-cftr Gating By 2ј-and 3ј-deoxy-atp-mentioning
confidence: 98%
See 2 more Smart Citations
“…Many compounds ( Amaral and Kunzelmann, 2007 ) and ATP analogues ( Cai et al, 2006 ;Bompadre et al, 2007 ) have been found to potentiate the activity of G551D-CFTR channels, but none of them could increase the activity of G551D-CFTR to WT levels. The binding site for only a very limited number of these CFTR " potentiatiors " has been identifi ed ( Bompadre et al, 2008 ). Interestingly, the 20-fold increase of the G551D-CFTR current by Cd 2+ is by far the most effective potentiation demonstrated for this disease-associated mutant.…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%